Tracking the GMPP of a solar photovoltaic water pumping system with an SMC controller in partial shading conditions - Khadija, Sabri; Ouadia, El Maguiri; Abdelmajid, Farchi (Institute of Advanced Engineering and Science, 2023)
The focus of this paper will be on the development of a photovoltaic (PV) pumping system that employs a DC-DC boost converter as an intermediate power conditioning unit in a centrifugal water pump powered by a brushless DC (BLDC) motor supplied by a solar photovoltaic panel (SPV). This work describes a particle swarm optimization (PSO) maximum power point tracking (MPPT) method compared with the gray wolf optimizer (GWO) method that are closed-loop with a sliding mode controller (SMC) in order to control the operational point of a solar PV in partial shading conditions (PSC), the DC-DC boost converter provides a low starting current for the BLDC motor, and the voltage source inverter (VSI) is used to perform electronic commutation of the BLDC motor. Furthermore, the BLDC motor's speed is regulated by the changeable DC link voltage. The system under consideration, as well as the control approaches employed, were created in the MATLAB/Simulink environment.